Temperature and the boreal-subarctic maximum in soil organic carbon - Swanson, David; Lacelle, Barbara; Tarnocai, Charles (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2000)
AbstractOn the plains of central North America and western Siberia, soil carbon storage and cover by organic soils are highest in the region with mean annual soil temperatures near 0° C, and generally decrease to the north and south. The location of this large soil carbon sink in the boreal and subarctic is probably due in part to the low heat availability in the soil as compared to the air in these regions. The thermal advantage of the air environment gives green plants a metabolic advantage over decomposers in the soil, which favors soil carbon accumulation. The thermal advantage of the air environment relative to the soil is greatest where mean annual soil temperatures are near or a few degrees below the lower limit of biological activity for cold-adapted soil organisms and plants, i.e. near 0° C.